Useable diffraction data from a multiple microdomain-containing crystal of Ascaris suum As-p18 fatty-acid-binding protein using a microfocus beamline - Gabrielsen, Mads (2012)
As-p18 is a fatty-acid-binding protein from the parasitic nematode Ascaris suum. Although it exhibits sequence similarity to mammalian intracellular fatty-acid-binding proteins, it contains features that are unique to nematodes. Crystals were obtained, but initial diffraction data analysis revealed that they were composed of a number of microdomains. Interpretable data could only be collected using a microfocus beamline with a beam size of 12 8 m.